Los planes de negocios y los proyectos de inversión: similitudes y diferencias - Andía Valencia, Walter (2013)
This article aims to provide information about the terms frequently used in the home and improvement of business activities, they are: the of business plans and investment projects; for such purpose describes the similarities and differences, making use of the concepts, objectives and structures defined in the literature of speciality.